2014
DOI: 10.1177/1362361313518124
|View full text |Cite
|
Sign up to set email alerts
|

Improving transportability of a cognitive-behavioral treatment intervention for anxiety in youth with autism spectrum disorders: Results from a US–Canada collaboration

Abstract: Anxiety disorders frequently co-occur in youth with autism spectrum disorders (ASD). In addition to developing efficacious treatments for anxiety in children with ASD, it is important to examine the transportability of these treatments to real-world settings. Study aims were to: a) train clinicians to deliver Facing Your Fears: Group Therapy for Managing Anxiety in Children with High-Functioning ASD (FYF) to fidelity; and b) examine feasibility of the program for novel settings. A secondary aim was to examine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(38 citation statements)
references
References 49 publications
2
34
0
2
Order By: Relevance
“…Because both ASD and social phobia are defined behaviorally, the overlap between the two disorders may result in misinterpretation of symptoms by clinicians. Significant comorbidity rates, ranging from 12–57% have been reported (e.g., de Bruin, et al, 2007; Farrugia & Hudson, 2006; Kuusikko et al, 2008; Reaven et al, 2015; Simonoff, et al, 2008), primarily in children and adolescents with HFA. Greater capacity for insight in individuals with HFA may contribute to increased awareness of social deficits and thus greater vulnerability to anxiety related to social evaluation (Weisbrot, Gadow, DeVincent, & Pomeroy, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because both ASD and social phobia are defined behaviorally, the overlap between the two disorders may result in misinterpretation of symptoms by clinicians. Significant comorbidity rates, ranging from 12–57% have been reported (e.g., de Bruin, et al, 2007; Farrugia & Hudson, 2006; Kuusikko et al, 2008; Reaven et al, 2015; Simonoff, et al, 2008), primarily in children and adolescents with HFA. Greater capacity for insight in individuals with HFA may contribute to increased awareness of social deficits and thus greater vulnerability to anxiety related to social evaluation (Weisbrot, Gadow, DeVincent, & Pomeroy, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…The persistence of anxiety, ADHD and tic symptoms suggests that more intervention is needed for HFA individuals. Modified cognitive behavioral treatments have been shown to be effective for youth with HFA (Chalfant, Rapee, & Carroll, 2007; Reaven, et al, 2015). It would be helpful to examine this type of treatment for OO individuals with anxiety, ADHD and/or tic symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Our participants were comparable to those included in previous efficacy studies [e.g., 11,21] with respect to baseline anxiety symptoms (e.g., [11] reported baseline SCARED scores of 33 and 27 for parent and childreport, respectively) and Full-Scale IQ (i.e., group mean within average limits, ranging from approximately 70 to 130), but it is difficult to determine whether ASD symptoms were comparable across studies, as most other studies describe their sample with respect to diagnostic categories rather than based on a measure of ASD symptoms. A strength of the current study is our use of the SCQ and SRS as continuous measures of ASD symptoms, with considerable range across individuals.…”
Section: Strengths and Limitationsmentioning
confidence: 75%
“…Despite the growing body of evidence for the efficacy of CBT for youth with ASD, there remains a gap between research-based and community implementation of these interventions [20]. Recently, program developers demonstrated the initial portability of the Facing Your Fears program in partnership with an outpatient service at a Pediatric Hospital in Nova Scotia, Canada (n = 16) [21]. Over half of group participants saw meaningful reductions in anxiety thus demonstrating, in a small sample, the promise of community implementation.…”
Section: Introductionmentioning
confidence: 99%
“…Although these results are promising, the studies were conducted in clinical research settings facilitated by experienced psychologists. To address the issue of transportability, effectiveness trials have investigated the delivery of FYF in: a home setting using a telehealth version (Hepburn, Blakeley‐Smith, Wolff, & Reaven, ); a community clinical setting delivered by clinicians previously inexperienced in implementing CBT with youth with ASD and anxiety (Reaven et al, ); and a school setting implemented by educators (Drmic et al, ). In each study, results showed positive treatment outcomes for participating children and youth, with a significant reduction in anxiety symptoms reported post‐intervention.…”
Section: Introductionmentioning
confidence: 99%